Crystal structure, DFT calculations and Hirshfeld surface analysis of 3-(4-methylphenyl)-6-nitro-1H-indazole - Ali Ben-Yahia; Youness El Bakri; Chin-Hung Lai; El Mokhtar Essassi; Joel T. Mague (Acta Crystallographica Section E: Crystallographic Communications, 2018)
The asymmetric unit of the title compound, C14H11N3O3, consists of two independent molecules having very similar conformations in which the indazole moieties are planar. The independent molecules are distinguished by small differences in the rotational orientations of the nitro groups. In the crystal, N—H...O and C—H...O hydrogen bonds form zigzag chains along the b-axis direction. Additional C—H...O hydrogen bonds link the chains into layers parallel to (10\overline{1}). These are connected by slipped π-stacking and C—H...π(ring) interactions.